Evaluasi Kinerja Portofolio Saham Dalam Indeks Bisnis-27 Berdasarkan Sektor Usaha: Perspektif Keuangan Syariah - Ali Yusuf Altikari; Yayat Sujatna (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study evaluates the performance of equity portfolios within the Bisnis-27 Index by economic sector through a Shariah-compliant framework using the Sharpe Ratio. Monthly historical price data for four constituent stocks CPIN (Primary Consumer Goods), KLBF (Healthcare), TLKM (Infrastructure/Telecommunications), and UNTR (Non-Primary Consumer Goods) from January 2021 to December 2025 were sourced from the Indonesia Stock Exchange, and Retail Sukuk yields served as the risk-free proxy. Descriptive analysis revealed differing average returns and volatilities across the stocks. Sharpe Ratio calculations ranked UNTR (0.828) and TLKM (0.794) highest, while CPIN (0.784) and KLBF (0.778) ranked lower. Sensitivity tests using Sukuk SR017 (5.90%) and SR018 (6.40%) benchmarks confirmed ranking stability. Bootstrap analysis produced 95% confidence intervals showing overlap between UNTR and TLKM Sharpe estimates, underscoring statistical uncertainty and indicating that their risk-adjusted performances are not significantly distinguishable. Advanced risk analyses including Value at Risk, Conditional Value at Risk, Sortino Ratio, Maximum Drawdown, Calmar Ratio, and EVT POT constructed a multidimensional risk profile, identifying TLKM as the most defensive sector and UNTR as the asset with the highest return potential and greatest tail risk. The discussion addresses post-pandemic macroeconomic implications and the pragmatic application of DSN-MUI Shariah screening criteria (debt ratio ≤ 45%, non-Halal income ≤ 10%) under Fiqh al-Waqīʿ. Strategic recommendations include overweight allocations to the non-primary consumer goods and telecommunications sectors as portfolio cores, cross-sector diversification to mitigate idiosyncratic risk, and dynamic portfolio management with periodic rebalancing. These findings offer practical guidance for Shariah-compliant investors, regulators, and scholars seeking to optimize sectoral investment decisions in Indonesia’s capital market.